FRI0076 What Inflammatory Marker Best Reflects Insulin Resistance in Rheumatoid Arthritis?. (9th June 2015) - Ursini, F.; Naty, S.; Bruno, C.; D'Antona, L.; Tripolino, C.; Nicolosi, K.; Rubino, M.; Savarino, F.; Grembiale, R.D.
Abstract : Background: Rheumatoid arthritis (RA) is characterized by an increased cardiovascular diseases (CVD) risk, estimated to be about 50% greater when compared to the general population[1]. Insulin resistance (IR), a key feature of the Metabolic Syndrome (MS) represents a well-recognized independent cardiovascular risk factor. RA has been epidemiologically correlated with an elevated prevalence of MS[2] independently of corticosteroids exposure[3], and the coexistence of RA with MS appears to be associated with a higher disease activity[4]. Objectives: Aim of this work was to examine the correlation between measures of inflammation and IR in RA patients. Methods: Height, weight and waist circumference (WC) were measured and Body Mass Index (BMI) was calculated with the standard formula. DAS28-CRP was used to evaluate disease activity. After overnight fasting, blood samples were obtained for laboratory evaluation including: complete blood count, plasma glucose, insulin, ferritin, erythrocyte sedimentation rate (ESR), High Sensitivity-CRP. Insulin resistance was estimated with the indirect measure Homeostasis Model Assessment of Insulin Resistance (HOMA-IR). Paired samples Student's t-test was used to compare means. The Pearson product-moment correlation coefficient was used to evaluate correlation between variables. Continuous variables that were not normally distributed were ln -transformed before analysis. A p -value <0.05 was considered statistically significant. Results: For the present study 100 RA patients (44 males, 56 females) and 100 age- and sex matched controls were recruited. Patients tended to be overweight and with a higher waist circumference compared to controls. In univariate correlational analysis HOMA-IR correlated significantly with age (r=0.34, p=0.001), BMI (r=0.69, p<0.0001), WC (r=0.66, p<0.0001), DAS28-CRP (r=0.25, p 0.02), ln(hs-CRP) (r=0.39, p=0.0002), ESR (r=0.43, p<0.0001), complement C3 (r=0.36, p=0.0006) and ln(Ferritin) (r=0.26, p=0.01). In controls, HOMA-IR correlated only with measures of obesity but not with inflammatory markers. Conclusions: In the present study we demonstrated that in RA patients, but not in controls, the indirect measure of insulin resistance HOMA-IR correlates with measures of inflammations. In this context, ESR is the single best parameter reflecting insulin resistance. References: Avina-Zubieta JA, Thomas J, Sadatsafavi M, Lehman AJ, Lacaille D: Risk of incident cardiovascular events in patients with rheumatoid arthritis: a meta-analysis of observational studies. Ann Rheum Dis 2012, 71:1524-1529. Zhang J, Fu L, Shi J, Chen X, Li Y, Ma B, Zhang Y: The risk of metabolic syndrome in patients with rheumatoid arthritis: a meta-analysis of observational studies. PLoS One 2013, 8:e78151. Toms TE, Panoulas VF, Douglas KM, Griffiths HR, Kitas GD: Lack of association between glucocorticoid use and presence of the metabolic syndrome in patients with rheumatoid arthritis: a cross-sectional study. Arthritis Res Ther 2008, 10:R145. da Cunha VR, Brenol CV, Brenol JC, Fuchs SC, Arlindo EM, Melo IM, Machado CA, de Castro Chaves H, Jr., Xavier RM: Metabolic syndrome prevalence is increased in rheumatoid arthritis patients and is associated with disease activity. Scand J Rheumatol 2012, 41:186-191. Disclosure of Interest: None declared